The two Koreas a contemporary history - Oberdorfer, Don (Basic Books, A member of the Perseus Books Group, 2014)
"Ever since Korea was first divided at the end of World War II, the tension between its northern and southern halves has riveted-and threatened to embroil-the rest of the world. In this landmark history, now thoroughly revised and updated in conjunction with Korea expert Robert Carlin, veteran journalist Don Oberdorfer grippingly describes how a historically homogenous people became locked in a perpetual struggle for supremacy-and how they might yet be reconciled"--